Síntomas psicopatológicos presentes en una muestra de mujeres condenadas en la cárcel San Diego de la Ciudad de Cartagena - Gulfo Madariaga, Andrea (Psicología, 2017)
In this research we will work with the internal prison San Diego, you will meet here to psychopathological symptoms of women deprived of liberty. The priority is to investigate and describe the presence of indicators of altered mood and the state of his mental health during their stay in prison.